Error monitoring and response inhibition in adolescents with bipolar disorders: An ERP study. - Stack, Kasey; Stim, Joshua J.; Sponheim, Scott R.; Collins, Paul; Luciana, Monica; Urošević, Snežana (Cognitive, Affective & Behavioral Neuroscience, 2025)
Cognitive control develops throughout adolescence, a high-risk period for bipolar disorders (BD) onset. Despite neurobehavioral abnormalities in adults with BD, there is minimal research investigating deviations in cognitive control in adolescents with BD. Cognitive control involves numerous processes. Identifying the specific neural abnormalities in adolescent BD could provide precise targets for novel interventions that improve illness outcomes. The present study administered a Go/No-Go (GNG) task to 98 adolescents (44 BD; 54 controls) to activate response inhibition and error processes and recorded EEG for event-related potentials (ERPs) analysis. Stimulus-locked N2 and P3 (response inhibition) and response-locked error-related negativity (ERN; early error detection) and error positivity (Pe; conscious error detection) were analyzed. Adolescents with BD had attenuated Pe mean amplitudes following failed inhibition trials. There were no group differences in other ERP amplitudes, including N2, P3, and ERN. The pattern of findings implicates conscious error detection impairment in adolescents with BD, without support for deficits in more automatic, earlier error detection. Impaired conscious error detection in adolescents with BD may be an early expression of BD pathophysiology and a possible intervention target for cognitive rehabilitation. Further studies are needed to examine Pe in BD across the lifetime.